Sedimentation in UHT high-protein dairy beverages: Influence of sequential preheating coupled with homogenisation or supplementation with carbohydrates. (February 2023) - de Souza, Alisson Borges; Xavier, Ana Augusta O.; Stephani, Rodrigo; Tavares, Guilherme M.
Abstract: Consumer demand for UHT high-protein dairy beverages is growing all around the world. To overcome the potential low stability of these products during processing and storage remains a great challenge for dairy industries. In this context, the potential of preheating treatment coupled with homogenisation or the addition of sucrose or corn soluble fibre on reducing the sedimentation level of UHT dairy beverages containing 10% w/w of protein and equivalent proportion of caseins to whey proteins were evaluated. The samples supplemented with sucrose or corn soluble fibre displayed a reduced overall particle size distribution, but equivalent amount of sediment compared with that in the control sample. The applied pretreatment promoted intense whey protein denaturation and reduced the overall particle size distribution and the amount of material sedimented compared with the control sample. The applied pretreatment has potential to improve the stability of UHT high-protein dairy beverages.